Base-stimulated 1,2-, 1,4-, and 1,6-eliminations in suitably substituted alkylidenesuccinates leading to natural and unnatural conjugated alkenyl(methyl)maleic anhydrides - Deore, Prashant S.; N. P. Argade (Journal of Organic Chemistry, 2014)
With dimethyl maleate as the starting material, facile stereoselective syntheses of natural and unnatural conjugated alkenyl(methyl)maleic anhydrides have been described. The key reactions were base-endorsed novel 1,2-, 1,4-, and 1,6-eliminations in the corresponding alkylidenesuccinate derivatives. The 1,2-eliminations in cyclic carbonate and sulfite by regioselective abstraction of methine protons with the respective release of CO2 and SO2 provided a conjugated ketone product. The characteristic 1,4- and 1,6-elimination reactions with respective release of acetone and mesylate furnished the corresponding unsaturated alcohols. The obtained allylic alcohols were transformed into conjugated alkenyl(methyl)maleic anhydrides via oxidation followed by a Horner-Wadsworth-Emmons reaction pathway in very good yields. The mechanistic aspects involved in these significant elimination reactions have also been described in brief.